2019
DOI: 10.1038/s41467-019-10543-z
|View full text |Cite
|
Sign up to set email alerts
|

Embedding laser generated nanocrystals in BiVO4 photoanode for efficient photoelectrochemical water splitting

Abstract: Addressing the intrinsic charge transport limitation of metal oxides has been of significance for pursuing viable PEC water splitting photoelectrodes. Growing a photoelectrode with conductive nanoobjects embedded in the matrix is promising for enhanced charge transport but remains a challenge technically. We herein show a strategy of embedding laser generated nanocrystals in BiVO 4 photoanode matrix, which achieves photocurrent densities of up to 5.15 mA cm −2 at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 166 publications
(101 citation statements)
references
References 44 publications
2
99
0
Order By: Relevance
“…In order to cope with the increasingly serious energy crisis, semiconductor photocatalysis has been considered as a prospective technique in response to the photocatalytic water splitting, carbon dioxide reduction, air pollutant removal, degradation of organic compounds and bacteria disinfection . To date, graphitic carbon nitride (g‐C 3 N 4 ), as a promising photocatalyst, has drawn considerable attention in these applications due to its appropriate band gap (2.7 eV), favorable chemical stability, zero toxicity and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…In order to cope with the increasingly serious energy crisis, semiconductor photocatalysis has been considered as a prospective technique in response to the photocatalytic water splitting, carbon dioxide reduction, air pollutant removal, degradation of organic compounds and bacteria disinfection . To date, graphitic carbon nitride (g‐C 3 N 4 ), as a promising photocatalyst, has drawn considerable attention in these applications due to its appropriate band gap (2.7 eV), favorable chemical stability, zero toxicity and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…The green antisolvent of EA was further extensively investigated to explore a variety of ACSs. Figure d,e,g,h shows that viable ACSs can be easily prepared containing Au and La:BaSnO 3 (LBSO) nanocrystals in EA with average sizes less than 5 nm, based on heating–melting–evaporation mechanism involved in pulsed laser irradiation . Embedding of the Au and LBSO nanocrystals led to increased average PCE from 19.09% to 20.35% and 20.61%, and champion PCE from 19.21% to 20.68% and 21.09%, respectively, indicating that these laser‐generated nanocrystals with high conductivity/carrier mobility are helpful for the extraction and transfer of photon‐generated carriers in PSCs (Figures S26–S29 and Tables S3–S4, Supporting Information).…”
Section: Discussionmentioning
confidence: 98%
“…Zeng [126]. Wang et al [127] reported the laser synthesis of ligand-free La:BaSnO 3 nanocrystals by PLAL, and by embedding this laser generated nanocrystals in BiVO 4 photoanode matrix, an enhanced charge transport for photoelectrode was achieved (Fig. 8e).…”
Section: Laser Synthesis Of Nanomaterials By Laser Ablation In Liquidmentioning
confidence: 99%